2015
DOI: 10.1111/risa.12368
|View full text |Cite
|
Sign up to set email alerts
|

Framing Effects in Narrative and Non‐Narrative Risk Messages

Abstract: Narrative messages are increasingly popular in health and risk campaigns, yet gain/loss framing effects have never been tested with such messages. Three experiments examined framing in narrative messages. Experiment 1 found that only the character's decision, not framing, influenced judgments about characters in a narrative derived from a prospect theory context. Experiment 2 found that a framing effect that occurred when presented in a decision format did not occur when the same situation was presented as a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 60 publications
(111 reference statements)
0
11
0
Order By: Relevance
“…However, this does not mean that the risk-comparison information itself is invalid for raising people’s understanding of the level of risk. Similar to the finding that narrative messages affect respondents’ decisions [52], a context that has the intention of persuasion rather than providing risk-comparison information probably causes public distrust. Use of cancer risk from radiation assumes absence of “zero risk.” Providers may think that this attitude is unacceptable; however, we highlight the fact that avoiding the use of information on “cancer risk from radiation and smoking risk” can lead the public to perceive that the risk is greater than the actual level.…”
Section: Discussionmentioning
confidence: 61%
“…However, this does not mean that the risk-comparison information itself is invalid for raising people’s understanding of the level of risk. Similar to the finding that narrative messages affect respondents’ decisions [52], a context that has the intention of persuasion rather than providing risk-comparison information probably causes public distrust. Use of cancer risk from radiation assumes absence of “zero risk.” Providers may think that this attitude is unacceptable; however, we highlight the fact that avoiding the use of information on “cancer risk from radiation and smoking risk” can lead the public to perceive that the risk is greater than the actual level.…”
Section: Discussionmentioning
confidence: 61%
“…In a study (Gray & Harrington, 2011), a narrative featuring a story character who exercised regularly and successfully got in shape (gain-framed) was more persuasive than a story with a character who did not exercise regularly and failed to get in shape (loss-framed). In another study, however, the predicted framing effect was not found when the information was presented as a narrative, suggesting that the traditional effects of gain-loss framing might not always apply in a narrative setting (Steinhardt & Shapiro, 2015). In light of the SCM, the utility of gain-loss framed narratives in improving quit intentions may change in accordance with smokers' current stages of change to quit smoking.…”
Section: Narrative Strategies To Promote Quit Intentions By Stages Of Changementioning
confidence: 90%
“…However, a significant proportion of the general public has low graphic literacy. Narrative information is often more powerful than statistical information [ 39 41 ].…”
Section: Literature Reviewmentioning
confidence: 99%